Effect of Self Control, Economic Literacy And Financial Management Of The Lifestyle Of Student Hedonism Working In Surakarta - Alvidasari, Yosefhin (STIE AUB Surakarta, 2018)
This study analyzes the influence of self control, economic literacy and financial management on the hedonism lifestyle of students working in Surakarta. Analytical techniques in this study consisted of instrument testing (validity test and reliability test), classical assumption test, multiple linear regression analysis, t test, F test and R2 test. This research yields regression equation Y = 9,307 + 0,158 X1 + 0,248 X2 + 0,176X3Based on the results of regression equation it can be seen that self-control, economic literacy and financial management have a positive effect on the lifestyle hedonism of students working in Surakarta. The result of statistical test t shows that self control, economic literacy and financial management partially have a positive and significant effect to the lifestyle variable of students working in Surakarta. The result of F statistic test in obtaining the value of 34,273 significant 0,000 <0,05. So that it can be concluded together self-control variables, economic literacy and financial management have a significant influence on lifestyle hedonism of students working in Surakarta. The result of adjucted R square test resulted 0,510 which means that the variability of hedonism lifestyle of students working in Surakarta can be explained by self control variable, economic literacy and financial management by 51% while the remaining 49% is explained by other unobserved variables.Keywords: self-control, economic literacy, financial management, hedonism lifestyle